The Effects of Iodinated Radiographic Contrast Media on Multidrug-resistant K562/Dox Cells: Mitochondria Impairment and P-glycoprotein Inhibition - Benjamaporn Supawat (2019)
Iodinated radiographic contrast media is used in cancer radiography for cancer diagnosis. The aim of this present study was to examine five iodinated radiographic contrast media (IRCM) (i.e., iohexol, iopamidol, iobitridol, ioxaglate, and iodixanol) in terms of their cytotoxicity, mitochondria membrane potential (ΔΨm), and P-glycoprotein function in multidrug resistant K562/Dox cancer cells and corresponding sensitive cancer cells. The cytotoxicity was determined by colorimetric resazurin reduction assay. The ΔΨm and P-glycoprotein function was measured using a noninvasive functional spectrofluorometry. Rhodamine B, fluorescence probe, was used to estimate ΔΨm. The kinetic of P-glycoprotein-mediated efflux pirarubicin was used to monitor P-glycoprotein function in multidrug resistant (MDR) cancer cells. The results showed that ioxaglate and iodixanol show similar efficacy in MDR cancer cells and for their corresponding sensitive cancer cells. Iopamidol, iohexol, and iobitridol showed higher efficacy in MDR cancer cells than for the corresponding sensitive cancer cells by approximately 2 fold. The results also showed no significant change in the |ΔΨm| values in treated K562 and K562/Dox cancer cells when compared to the non-treated K562 and K562/Dox cancer cells. However, there were notable changes detected for iobitridol and iodixanol at 50 mgI/mL. Similarly, the results showed significant differences in P-glycoprotein function of K562/Dox cancer cells after treatment with IRCM when compared to the non-treated K562/Dox cancer cells, with iohexol and iodixanol being the notable exceptions once again. In this present study, IRCM exhibited cytotoxicity on MDR cancer cells and their corresponding sensitive cancer cells. IRCM also showed potential as an anticancer agent in the future.